Pengaruh Komptensi Dokter, Sarana Prasarana Dan Pelayanan Terhadap Kepuasan Pasien Rawat Inap Rumah Sakit Cikunir - Virgia Widyawati; Subagiyo (Jurnal Satya Mandiri Manajemen dan Bisnis, 2018)
In this study, entitled "The Effect of Physician Competence, Facilities And Services Inpatient Satisfaction Cikunir Hospital", the authors examined whether there is a positive relationship between the competence of doctors, facilities and services to the satisfaction of hospital inpatients Cikunir. The purpose of this study is to know: Analyze how the influence of doctor's competence, facilities and services to patient satisfaction either partially or simultaneously. The method used in this research is quantitative research is research explanatory survey with cross sectional approach sampling method in this research is the method of probability sampling, the number of hospitalized patients who will be the respondent is calculated using the formula Slovin (Suliyanto, 2006: 100) number the respondents of this study with the error rate of 10% were 100 respondents. Using SEM analysis it was found that the partial competence of the doctor did not significantly affect patient satisfaction, infrastructure and services have a significant impact on patient satisfaction. Simultaneously the competence of doctors, facilities and services affect the satisfaction of inpatients of Cikunir hospital.